Constructing the sustainable workplace interior through material practices (ARSNET, 2025)
This study discusses the design development of a sustainable workplace interior, using PITA office—a furniture company in Indonesia—as the context of study. The design aims to create a sustainable office environment that reflects the company's commitment to sustainability, particularly in relation to various interior material practices. This study applies Nirmal Kishnani's six principles of sustainable design within the Asian context to the interior design of the PITA office, encompassing the principles of efficacy, ecology, wellness, embeddedness, advocacy, and integration. A qualitative approach was implemented through observation, documentation, and interviews to analyse the context based on the six sustainable design principles and inform further design propositions. The study explores how such sustainable principles can be translated materially to provide office interior design that is responsible for users and the environment. It identifies the material criteria relevant for designing a sustainable workplace interior, which supports energy efficiency, reduces environmental impact, creates a connection with locality, and provides well-being for its users. Such material practice criteria contribute to the way sustainable interiors can be achieved holistically as part of an environmentally responsible design approach.